Agricultural Productivity and Non-Farm Employment : Evidence from Bangladesh - Shilpi, Forhad; Emran, Shahe (World Bank, Washington, DC, 2016)
This paper provides evidence on the impacts of agricultural productivity on employment growth and structural transformation of non-farm activities. To guide the empirical work, this paper develops a general equilibrium model that emphasizes distinctions among non-farm activities in terms of tradable-non-tradable and the formal-informal characteristics. The model shows that when a significant portion of village income is spent on town/urban goods, restricting empirical analysis to the village sample leads to underestimation of agriculture's role in employment growth and transformation of non-farm activities. Using rainfall as an instrument for agricultural productivity, empirical analysis finds a significant positive effect of agricultural productivity growth on growth of informal (small-scale) manufacturing and skilled services employment, mainly in education and health services. For formal employment, the effect of agricultural productivity growth on employment is found to be largest in the samples that include urban areas and rural towns compared with rural areas alone. Agricultural productivity growth is found to induce structural transformation within the services sector with employment in formal/skilled services growing at a faster pace than that of low skilled services.